2022
DOI: 10.53730/ijhs.v6n2.10937
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation and trigger band technique on groin adductor strain in athletes

Abstract: Aim of the study: In athletes, groin pain-related adductor strain is a common problem in sports medicine, like groin injuries, so the study investigated the effect of Photobiomodulation (905 nm) and Trigger Band Technique (TBT) on handball athletes' groin adductor strain. Methods: Forty handball athletes with adductor groin strain were divided into an experimental group (A) that received Diode laser 905nm, TBT, and medical treatment, while control group (B) received sham laser with TBT and medical treatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Musculoskeletal pain rating scale and time to return-to-play data were collected. Six studies evaluated pain by the visual analogue scale (3,50), modified numerical rating scale (52), pain pressure threshold (53), and numeric pain rating scale (57). The findings indicated a positive effect on pain reduction for PBM vs. control groups, SMD = 1.03, SE = 0.22, 95% CI = [0.43–1.63], p = 0.0089 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal pain rating scale and time to return-to-play data were collected. Six studies evaluated pain by the visual analogue scale (3,50), modified numerical rating scale (52), pain pressure threshold (53), and numeric pain rating scale (57). The findings indicated a positive effect on pain reduction for PBM vs. control groups, SMD = 1.03, SE = 0.22, 95% CI = [0.43–1.63], p = 0.0089 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Two researchers who published on the effects of PBM on pain in injured athletes were contacted to locate additional studies and referred studies were evaluated against inclusion criteria. After searching the reference list of relevant articles and Google Scholar, 2 additional articles were found making the total number of articles included to be 6 (3,42,50,52,53,57). Figure 1 demonstrates the process used to retain included studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…These mutations are found in around 80% of patients with the triple-negative (TN) form, 10% of patients having luminal A, 30%with luminal B, and the HER2-enriched form represents approximately 70% [47][48].The existence of mutant p53 in breast cancer, particularly the TN subtype, may serve as a biomarker or therapeutic target. In breast cancer, missense mutations dominate, and more than 81% occur in exons 5-8 [49][50]. Exons 4 and 10 have approximately 10% and 6% respectively.…”
Section: Second: P53 and Breast Cancermentioning
confidence: 99%
“…Mutations in patients with ductal breast cancer are more common than those with the lobular form, and more prevalent in lymph node-positive than lymph node-negative tumors. Furthermore, oestrogen receptor (ER)-negative tumors are more numerous than ER-positive tumors, whereas HER2-positive cases are more prevalent than HER2-negative [49][50].It has been shown that p53 mutations are common in some breast cancers and usually represent an early occurrence [51][52][53][54]. The p53 mutation has been observed in 10-30% of ductal carcinomas in situ (DCIS) [55].…”
Section: Second: P53 and Breast Cancermentioning
confidence: 99%